Piper betel leaves induces wound healing activity via proliferation of fibroblasts and reducing 11β hydroxysteriod dehydrogenase-1 expression in diabetic rat - Nur Amalina Ghazali; Azree Elmy; Lee Chee Yuen; Nurul Zaidah Sani; Srijit Das; Farihah Suhaimi; Rafizul Yusof; Nurul Huda Yusoff; Zar Chi Thent (Journal of Ayurveda and Integrative Medicine, 2016)
Background: Increased oxidative stress and stress enzyme 11β hydroxysteriod dehydrogenase-1 (11β HSD-1) served as the major contributing factors for delayed wound healing in diabetes mellitus (DM). Piper betel (PB) leaves are reported to possess anti-diabetic, anti-oxidant and anti-microbial properties. Objective: The objective was to investigate the effectiveness of topical application of PB leaves extract on oxidative stress and 11β hydroxysteriod dehydrogenase-1 (11β HSD-1) expression in diabetic wounds. Materials and methods: A total 64 male Sprague-Dawley rats were randomly chosen. The experimental rats received a single intramuscular injection of streptozotocin (45 mg/kg). Four full thickness (6 mm) wounds were created on the dorsum of each rat. The animals were equally divided (n = 8) into four groups based on the days of treatment (i.e. days 3 and 7): Control (Ctrl), diabetic untreated (DM-Ctrl), diabetic treated with 1% silver nitrate cream (DM-SN) and diabetic treated with 50 mg/kg of P. betel leaves extract (DM-PB). The rats were sacrificed on day 3 and 7 of post wound creations. Results: Following day 7 wound creation, topical application of PB extract showed significant increase in hydroxyproline content, superoxide dismutase (SOD) level and decreased malondialdehyde (MDA) level, 11β-HSD-1 enzyme expression in the diabetic wounds compared to untreated diabetic wounds. The results were supported by the observations based on histological and ultrastructural features of the wound tissue applied with PB extract. Conclusion: PB leaves extract improved the delayed wound healing in diabetes mellitus by decreasing the oxidative stress markers and 11β HSD-1 expression.